2011
DOI: 10.1017/s0714980811000092
|View full text |Cite
|
Sign up to set email alerts
|

À mots couverts: le regard des aînés et des soignants sur la communication quotidienne et ses manifestations d’âgisme implicite

Abstract: The aim of this exploratory study was to better understand interpersonal communication between frail elders and caregivers in the context of long-term care giving. In addition, in light of the Communication Accommodation Theory, the goal was to determine the extent to which communication can be a transmitter of ageism, particularly of implicit ageism. A total of 26 semi-structured interviews were conducted among elders and caregivers of a Quebec long-term care facility. Results suggest a close convergence betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…We were able to identify only one study focusing on ageism in health care that explicitly considers positive stereotypes about ageing (Gunderson et al 2005). Research on long term care more often recognizes the positive aspect of ageism (Lagacé et al 2011;Natan et al 2013;Wells et al 2004) although it rarely takes a central place in the analysis. A noteworthy exception is the study of Taverna et al (2014) who link the desire on the part of long-term care staff to respect residents' independence and autonomy due to their age (positive discrimination) to improper oral hygiene (a negative health outcome).…”
Section: Comparison Of Research On Ageism In Health and Long-term Carementioning
confidence: 99%
“…We were able to identify only one study focusing on ageism in health care that explicitly considers positive stereotypes about ageing (Gunderson et al 2005). Research on long term care more often recognizes the positive aspect of ageism (Lagacé et al 2011;Natan et al 2013;Wells et al 2004) although it rarely takes a central place in the analysis. A noteworthy exception is the study of Taverna et al (2014) who link the desire on the part of long-term care staff to respect residents' independence and autonomy due to their age (positive discrimination) to improper oral hygiene (a negative health outcome).…”
Section: Comparison Of Research On Ageism In Health and Long-term Carementioning
confidence: 99%
“…These authors claim that all humans, regardless of their age, participate in the process of implicit ageism, and that '(…) one of the most insidious aspects of ageism is that it can operate without conscious awareness, control, or intention to harm' (Levy and Banaji, 2002: 50). Implicit ageism is the root of ageist practices (Levy and Banaji, 2002), such as the ageist language used by LTC workers (Lagacé et al, 2011, Running title: On studying ageism in long-term care 25 2012). Iversen et al (2009: 16) argue that when a physician has a rigid schedule and scarce time, 'implicit ageism may result in even less time for the elderly patients combined with a tendency to ascribe their complaints to old age'.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have found associations between cognitive impairment, ADL impairment, and behavioral problems and care transitions, other studies found no associations (Lieberman & Kramer, 1991; Spitznagel et al, 2006). This suggests that perhaps the link between the characteristics of the person with dementia and care transition decisions is mediated by other variables such as family caregivers’ feelings of burden and their feelings about their interactions and relationship with the care recipient.…”
Section: Predictors Of Transitions In Carementioning
confidence: 91%
“…As noted above, this form of avoidance and disengagement from the relative with dementia may translate into focus on instrumental tasks, away from sustained interactions with the person with dementia (Miron et al, 2019a). Recent work suggests that dementia caregivers often adopt task-focused strategies (Iavarone et al, 2014;Lagacé et al, 2011), which may allow them to avoid interactions with the family member with dementia with whom they find it difficult to connect meaningfully. Decreased desire for face-to-face interaction can also take the form of an increased desire to transition the care recipient to congregate care.…”
Section: Fear Of Incompetencementioning
confidence: 99%